Modeling the Fate of Listeria monocytogenes and Salmonella enterica on Fresh Whole and Chopped Wood Ear and Enoki Mushrooms - Megan L. Fay; Joelle K. Salazar; Josephina George; Nirali J. Chavda; Pravalika Lingareddygari; Gayatri R. Patil; Vijay K. Juneja; David T. Ingram (Journal of Food Protection, 2023)
Two recent foodborne illness outbreaks linked to specialty mushrooms have occurred in the United States, both representing novel pathogen-commodity pairings. Listeria monocytogenes and Salmonella enterica were linked to enoki and wood ear mushrooms, respectively. The aim of this study was therefore to examine the survival of both L. monocytogenes and S. enterica on raw whole and chopped enoki and wood ear mushrooms during storage at different temperatures. Fresh mushrooms were either left whole or chopped and subsequently inoculated with a cocktail of either S. enterica or rifampicin-resistant L. monocytogenes, resulting in an initial inoculation level of 3 log CFU/g. Mushroom samples were stored at 5, 10, or 25°C for up to 7 d. During storage, the population levels of S. enterica or L. monocytogenes on the mushrooms were enumerated. The primary Baranyi model was used to estimate the growth rates of both pathogens and the secondary Ratkowsky square root model was used to model the relationship between growth rates and temperature. Both L. monocytogenes and S. enterica survived on both mushroom types and preparations at all temperatures. No proliferation of either pathogen was observed on mushrooms stored at 5°C. At 10°C, moderate growth was observed for both pathogens on enoki mushrooms and for L. monocytogenes on wood ear mushrooms; no growth was observed for S. enterica on wood ear mushrooms. At 25°C, both pathogens proliferated on both mushroom types with growth rates ranging from 0.43 to 3.27 log CFU/g/d, resulting in 1 log CFU/g increases in only 0.31 d (7.44 h) to 2.32 d. Secondary models were generated for L. monocytogenes on whole wood ear mushrooms and S. enterica on whole enoki mushrooms with goodness-of-fit parameters of r2 = 0.9855/RMSE = 0.0479 and r2 = 0.9882/RMSE = 0.1417, respectively. Results from this study can aid in understanding the dynamics of L. monocytogenes and S. enterica on two types of specialty mushrooms.